Full Fuzzy Parameterized Soft Set Theory with Decision Making (Journal of Pure and Applied Sciences (Science Forum), 2025)
In this present work, we consider the algebraic operations on full fuzzyparameterized soft set and hence study some of its properties. Furthermore, we giveapplication of this concept in solving decision making problem by developing analgorithm, which is demonstrated with a numerical example to validate thetheoretical arguments.